A spatiotemporal gradient in the anthropization of Pyrenean landscapes. Preliminary report. (15th April 2021) - Rull, Valentí; Vegas-Vilarrúbia, Teresa
Abstract: A preliminary analysis of the timing of landscape anthropization in the southern-central Pyrenees shows the occurrence of an elevational gradient from the Bronze Age (basal belts) to the Middle Ages (alpine belts). This relationship is statistically significant and suggests an average anthropization rate of 40 m in elevation per century. The elevational gradient is most clear between the Bronze Age and the Roman occupation, suggesting a progressive upward anthropization trend from the south with the likely involvement of Iberian cultures. During the Middle Ages, a massive anthropization pattern of subalpine/alpine areas is observed; this pattern is chronologically consistent with the incursion of northern cultures crossing the Pyrenees and the development of extensive high-mountain pastoralism and horizontal transhumance. In general, the progression of upward anthropization has occurred during warm climatic phases. Further work is needed to confirm these observations, especially in areas with few available paleoecological studies, notably the basal and montane belts. It could be interesting to develop similar studies of other Pyrenean regions and other mountain ranges. Highlights: A general anthropization trend from the Bronze Age to the Middle Ages in the central Pyrenees. This spatiotemporal gradient is based on the existing palynological studies. The trend should be confirmed with future studies, especially in the basal and the montane belts. Further studies should verify whether similar spatiotemporal patterns occur in other mountain ranges.